Small-Signal Stability Analysis of The Hydrokinetic Energy Harnessing connected to The Grid - Wan Ismail, Ibrahim; Mohd Rusllim, Mohamed; Raja Mohd Taufika, Raja Ismail (IOP Publishing, 2020)
This paper presents the modelling of the hydrokinetic system for the small-signal stability analysis under the small disturbances due to variation and fluctuation of water velocity in the river or marine. The complete modelling of the hydrokinetic system consists of vertical axis H-Darrieus turbine, direct-drive permanent magnet synchronous generator (PMSG), back-to-back converter and the grid network. By linearising all the equation around the steady-state value, the dynamic equation of the hydrokinetic system is derived. The stability of the system is tested with and without the PI controller. The eigenvalues analysis-based approaches have been used to investigate the stability of the system under the small disturbances. The findings show, the stability of the hydrokinetic system with PI controller is improved up to 57.82% by reducing the oscillation frequency at the Rotor Side Converter (RSC).